American Cancer Society Colorectal Cancer Survivorship Care Guidelines. (8th September 2015) - El‐Shami, Khaled; Oeffinger, Kevin C.; Erb, Nicole L.; Willis, Anne; Bretsch, Jennifer K.; Pratt‐Chapman, Mandi L.; Cannady, Rachel S.; Wong, Sandra L.; Rose, Johnie; Barbour, April L.; Stein, Kevin D.; Sharpe, Katherine B.; et al.
Abstract : Answer questions and earn CME/CNE Colorectal cancer (CRC) is the third most common cancer and third leading cause of cancer death in both men and women and second leading cause of cancer death when men and women are combined in the United States (US). Almost two‐thirds of CRC survivors are living 5 years after diagnosis. Considering the recent decline in both incidence and mortality, the prevalence of CRC survivors is likely to increase dramatically over the coming decades with the increase in rates of CRC screening, further advances in early detection and treatment and the aging and growth of the US population. Survivors are at risk for a CRC recurrence, a new primary CRC, other cancers, as well as both short‐term and long‐term adverse effects of the CRC and the modalities used to treat it. CRC survivors may also have psychological, reproductive, genetic, social, and employment concerns after treatment. Communication and coordination of care between the treating oncologist and the primary care clinician is critical to effectively and efficiently manage the long‐term care of CRC survivors. The guidelines in this article are intended to assist primary care clinicians in delivering risk‐based health care for CRC survivors who have completed active therapy.CA Cancer J Clin 2015;65:427–455 . ©2015 American Cancer Society.